(untitled) (Research, Society and Development, 2024)
In order to expand health actions, the Health Reform Movement and the creation of the Unified Health System - SUS became a right of all and a duty of the State, which aimed to promote the healthy life of Brazilian citizens. Objective: to analyze the insertion of the Physical Education professional in the SUS, reinforcing body practices and physical activity as a priority action in the area of public health. Methodology: this is a Narrative Review of Literature with a descriptive approach and qualitative nature. Results: demonstrated the systematization of 15 articles and 5 methodology books, published between the years 2019 and 2024 that deal with the insertion of the Physical Education professional in Public Health. Considerações Finais: considerando que a inserção do profissional de Educação Física estar vinculado a área da saúde, este profissional pode contribuir com as práticas corporais e atividades físicas como ação prioritária para a população brasileira e demandas do SUS.